Augmented reality coloring book / Nurul Ain Shafawani Shahimi ... [et al.] - Shahimi, Nurul Ain Shafawani; Zaini, Hazrati; Sabri, Nurbaity; Mohd Johari, Nur Farahin; Ishak, Norshahidatul Hasana (2020)
Children can benefit from using mobile technologies in classroom for learning purposes. A few studies mentioned there exists a lack of technologies applied at schools. Creating entertaining educational books not only requires visually stimulating content but also means for student to interact, create, and express themselves. Many researches indicates that use of augmented reality technologies in teaching helps children to get motivated and engaged and it is beneficial for children's memory retention. In this paper, a new type of mixed-reality book experience, which augments an educational coloring book with user-generated threedimensional content is presented. This study aims at creating an augmented reality (AR) book for 4-6 years old children and on the understanding of how AR can affect engagement and how it can support and help learning coloring in terms of memorization. Engagement testing was conducted on 30 students based on Student Engagement Scale (SES) which are divided into categories of emotional, cognitive and behavioral of the students while using the application. The analyzed results point out towards the fact that AR could help children of preschool age in classroom education by positively affecting their coloring skills, memory retention and increasing their engagement and motivation.